Chinese traditional motifs in contemporary European music - Chai, Wei (Música Hodie, 2023)
Nowadays, music demands constantly change respectively to listeners’ needs. Owing to this fact, old music genres fade into the background. However, traditional music leaves a mark largely imprinted in not only Chinese music, but also world music. Thus, it is important to investigate contribution of traditional Chinese music to the modern European music. Respondents from various Chinese music departments were surveyed to examine the contribution of traditional Chinese culture to various types of contemporary European music. A list of Chinese folk music identification factors was also compiled to better understand the perception of Chinese traditional motifs in contemporary European music. To study this problem, at the first stage of the study a large number of musical works from different European countries was analyzed (the music of such countries as Great Britain, Germany and France was analyzed within the framework of this work). The finding shows that common features of traditional Chinese motifs are domination of monophonic performance, enormous variation of percussion, "contemplative mood", pentatonic scale without semitones, and availability of stringed instruments. In addition, the second step of investigation shed light on the contribution of Chinese tradition music to music of different European countries. In the last stage, tracks in which respondents thought Chinese folk motifs existed were examined by means of a quantitative analysis of musical scores to identify common characteristics (rhythm, skips, and similar melodies). This analysis helped to better understand the main characteristics of Chinese folk music's contribution to contemporary European music. As the analysis showed, regardless of the country to which this or that track belongs, there are common characteristics - the singing of steady steps and the descending melody with a subsequent rise by one tone or semitone. According to the result, British modern music has more Chinese folk motifs (15 from 50 randomly chosen works), whereas German music contains only 9 from 50 works. At the same time, French music has only 1 out of 50 Chinese folk motifs. Also, all respondents were interviewed to determine common adjectives, which help to characterize Chinese folk music. The finding shows that the most popular adjectives are "mesmerizing", "intriguing", "intricate", "calm", "mysterious", "sublime" and "soothing". Obtained results contribute to the research of Chinese traditional music perception and its contribution to European contemporary music. Furthermore, the framework used in this research is new and can be applied in subsequent works in this area of research.